Pola Konsumsi Karyawan Tetap dan Kontrak dalam Perspektif Etika Ekonomi Islam: Studi pada PT. Sadhana Purwosari Pasuruan - Ningsih, Rohma; Maghfur, Ifdlolul; Mukhsinin Syu’aibi, Moh. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze differences in consumption patterns between permanent and contract employees at PT. Sadhana Purwosari Pasuruan within the framework of Islamic economic ethics. Using a qualitative descriptive approach, data were collected through in-depth interviews and direct observations to understand how employment status influences economic behavior. The findings reveal that permanent employees, supported by income stability and job security, exhibit more balanced and planned consumption behavior. Their spending patterns reflect Islamic ethical principles such as tawazun (moderation), avoidance of israf (wastefulness), and the spirit of zuhud (simple living), as well as regular engagement in infaq and charitable giving. Conversely, contract employees tend to allocate a greater portion of their income to immediate needs and consumptive spending, often exceeding their financial capacity. Limited income stability and financial uncertainty hinder the implementation of Islamic consumption principles. The study concludes that employment stability significantly shapes one’s ability to practice ethical consumption. Therefore, it recommends the implementation of financial literacy programs based on Islamic ethical values and the development of workplace spiritual guidance to encourage responsible and balanced consumption behavior.